2014
DOI: 10.1080/17486025.2014.933891
|View full text |Cite
|
Sign up to set email alerts
|

Discrete element analysis of breakage of irregularly shaped railway ballast

Abstract: In order to reduce the maintenance costs of ballasted railway track and improve passenger comfort, the railway ballast particle breakage and its effect on track settlement need to be better understood. The failure process of individual railway ballast loaded between flat platens is simulated using the discrete element method, considering its irregular shape with the incorporation of parallel bonds. The tensile strength, the stress of a survival probability of 37% of samples, is obtained and compared with labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…As time progresses, trains travel faster, railways become longer and convey heavier goods, and more stringent safety standards mandate a higher level of below-rail alignment for longer design periods. However, the main below-rail ballast layer, which is referred to in the present study as the ballast embankment, eventually becomes misaligned due to ballast breakage and rearrangement [1][2][3][4]. As a result, the embankment is prone to subsidence and lateral spreading, which undermines the safety of the tracks.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…As time progresses, trains travel faster, railways become longer and convey heavier goods, and more stringent safety standards mandate a higher level of below-rail alignment for longer design periods. However, the main below-rail ballast layer, which is referred to in the present study as the ballast embankment, eventually becomes misaligned due to ballast breakage and rearrangement [1][2][3][4]. As a result, the embankment is prone to subsidence and lateral spreading, which undermines the safety of the tracks.…”
Section: Introductionmentioning
confidence: 86%
“…Railway ballast is usually produced by blasting and/or fragmenting a rock mass, and hence exhibits variable angularities. Past studies [3,31,32] have demonstrated the importance of accurately modeling the particle angularities, and suggested that reflecting angularities in simulations better reproduces the actual behavior of the ballast. To achieve this, four 'clump templates' were developed: trapozoidal, triangular, rectangular and hexagonal (Table 2), which account for the major geometric shapes of ballast infills.…”
Section: Ballastmentioning
confidence: 99%
“…The method for simulating the ballast bed can remedy the shortcoming of FEM in characterizing the meso-mechanical behaviour of ballast. Henceforth, it has been employed widely to studies regarding mechanical behaviours, such as ballast degradation [9][10][11], ballast fouling [12], ballast breakage [13,14], and polyurethane-reinforced ballasts [15] in ballasted railway tracks. The model constructions of irregular ballasts involve primarily the clump of overlapped spheres [16], cluster formed by bonding spheres [17], polyhedrons [18][19][20], and dilated polyhedron elements [21].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been conducted to investigate ballast breakage and its influence on the mechanical response of ballast. Discrete element modeling (DEM) was often used in the studies (Lobo-Guerrero and Vallejo, 2006, Hossain et al, 2007, Indraratna et al, 2009, Lu and McDowell, 2010, Yan et al, 2014, Wang et al, 2017. Yan et al (2014) and Wang et al (2017) employed 3dimensional (3D) DEM to study the breakage mechanism of a single ballast stone under uniaxial compressive loading.…”
Section: Introductionmentioning
confidence: 99%
“…Discrete element modeling (DEM) was often used in the studies (Lobo-Guerrero and Vallejo, 2006, Hossain et al, 2007, Indraratna et al, 2009, Lu and McDowell, 2010, Yan et al, 2014, Wang et al, 2017. Yan et al (2014) and Wang et al (2017) employed 3dimensional (3D) DEM to study the breakage mechanism of a single ballast stone under uniaxial compressive loading. Lu and McDowell (2010) also adopted 3D DEM to simulate breakable ballast by attaching small particles to unbreakable clumps and subjected the ballast assembly to monotonic and cyclic loads under triaxial condition.…”
Section: Introductionmentioning
confidence: 99%